2012
DOI: 10.5414/cnx77s101
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency external muscle stimulation in acute kidney injury (AKI): potential shortening of its clinical course

Abstract: Background: The prognosis of acute kidney injury (AKI) is markedly influenced by the degree of muscle protein catabolism. Since the current therapeutic strategies are rather limited, for the first time, we attempted to attenuate the hypercatabolism by high tone electrical muscle stimulation (HTEMS) in AKI patients. This kind of therapy may lower protein degradation via its effect on muscle activity as well as improving insulin resistance. Moreover, electrotherapy may improve renal function due to circulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…There are few studies on NMES training during hemodialysis in patients with chronic kidney disease. NMES has been found to stabilize blood pressure during hemodialysis [136] and to improve dialysis efficacy [137,138]. Also, improved exercise capacity has been found [137].…”
Section: Clinical Recommendation For Nmes Applicationsmentioning
confidence: 99%
“…There are few studies on NMES training during hemodialysis in patients with chronic kidney disease. NMES has been found to stabilize blood pressure during hemodialysis [136] and to improve dialysis efficacy [137,138]. Also, improved exercise capacity has been found [137].…”
Section: Clinical Recommendation For Nmes Applicationsmentioning
confidence: 99%
“…Third, a greater LBM decreased the probability of developing creatinine-based AKI. This finding is substantiated by the work of Liu et al 48 where they found that underweight patients had a greater chance of developing AKI in ICU as adequate nutritional intake is thought to reduce ICU length of stay and improve chances of recovery 49 , 50 .…”
Section: Discussionmentioning
confidence: 82%
“…Body mass index may be an important modifiable risk factor for mortality in patients presenting with AKI. Achieving an adequate nutritional intake in sufferers with AKI is hypothesised to reduce length of stay and improve rehabilitation potential by preventing or reducing muscle wastage [ 20 , 21 ]. However, the proposed benefits of body compositional preservation have never been studied.…”
Section: Discussionmentioning
confidence: 99%